Tobacco control measures in COVID-19 recovery: an opportune time to restore equity and planetary health - Daniel Tzu-Hsuan Chen (Komiyama Printing Co. Ltd, 2022)
Tobacco intersects with the COVID-19 pandemic not only in terms of health consequences, but also environmental change and planetary health. Tobacco use exacerbates inequalities, causes catastrophic environmental degradation and climate change and adds burdens to COVID-19-related mortality, which are major challenges to recovery from the COVID-19 pandemic. However, the pandemic has provided a chance to combat tobacco use and accelerate efforts to alleviate these challenges in response. The MPOWER measures introduced by the World Health Organization Framework Convention on Tobacco Control (WHO FCTC) can play a crucial role in COVID-19 recovery to fight tobacco use and contribute to sustainable and equitable development. To accelerate recovery, it is critical to call for actions for governments and policy-makers to strengthen synergies and coordinate policy actions emphasising tobacco control and cessation across equity, public health, and climate actions as global authorities pledge to achieve the Sustainable Development Goals (SDGs) and net zero emissions targets as part of the Climate Change Conference 2021 (COP26).